Implementation Of The Iwaka District Expansion Policy In The Perspective Of Asymmetric Decentralization In Papua - Timoty Yusuf Salama; Sulthon Rohmadin (International Journal Labs, 2025)
This study examines the implementation of the Iwaka District expansion policy in Mimika Regency within the framework of asymmetric decentralization in Papua. The policy reflects an effort to operationalize Indonesia’s special autonomy mandate (Law No. 2 of 2021) by extending state presence and improving public service delivery in geographically remote areas. Using a qualitative descriptive approach and a single-case design, the research collected data through in-depth interviews, field observations, and document analysis conducted in August 2025. Data were analyzed using the Miles and Huberman interactive model, focusing on four dimensions of policy implementation proposed by Edwards III—communication, resources, disposition, and bureaucratic structure—complemented by Grindle’s policy content-context framework and Rondinelli’s theory of asymmetric decentralization. The findings indicate that although the Iwaka expansion has not fully met administrative criteria under Government Regulation No. 17 of 2018, its implementation demonstrates strong social legitimacy and affirmative intent to enhance service accessibility. The main challenges include limited human resources, inadequate infrastructure, and weak inter-agency coordination. Overall, the Iwaka case highlights that successful implementation of asymmetric decentralization depends not only on legal compliance but also on contextual governance capacity, local participation, and institutional adaptation. The study concludes that the Iwaka expansion serves as a strategic instrument for strengthening local governance and state legitimacy in Papua’s special autonomy region.